Wage setting patterns and monetary policy: International evidence - Giovanni Olivei; Silvana Tenreyro (Federal Reserve Bank of Boston, 2010)
Systematic differences in the timing of wage setting decisions among industrialized countries provide an ideal framework to study the importance of wage rigidity in the transmission of monetary policy. The Japanese Shunto presents the best-known case of bunching in wage setting decisions: From February to May, most firms set wages that remain in place until the following year; wage rigidity, thus, is relatively higher immediately after the Shunto. Similarly, in the United States, a large fraction of firms adjust wages in the last quarter of the calendar year. In contrast, wage agreements in Germany are well spread within the year, implying a relatively uniform degree of rigidity. We exploit variation in the timing of wage setting decisions within the year in Japan, the United States, Germany, the United Kingdom, and France to investigate the effects of monetary policy under different degrees of effective wage rigidity. Our findings lend support to the long-held, though scarcely tested, view that wage rigidity plays a key role in the transmission of monetary policy.
Keywords: E1; E52; E58; E32; E31; 330; Geldpolitik; Transmissionsmechanismus; Lohnrigidität; Lohnverhandlungen; Zeit; Industriestaaten